Pengembangan Alat Hand Sanitizer Otomatis dengan Metode Research and Development Untuk Menjaga Kesehatan - Herfandi Herfandi; Gilang Ginanta; Eko Purwirawansyah; Kamal Prihandani (Jurnal Teknologi, 2022)
Covid-19 is the type of virus that causes the disease SARS-CoV-2. The government has implemented policies to prevent the spread of Covid-19, one of which is to wash hands regularly using hand sanitizer. However, the use of hand sanitizers is currently still widely applied manually, namely by pressing the pump lever on the hand sanitizer. Therefore, it is important to develop an automatic hand sanitizer. The research and development (R & D) method is able to create a product that has a high validity value because it goes through a series of testing and validation stages. This research is developing an automatic hand sanitizer with research and development methods. The result of this research is an automatic hand sanitizer device based on the Arduino Uno microcontroller with two servo motors as the driving force for the hand sanitizer and an ultrasonic sensor as input. The tools developed were proven to be more effective than manual tools based on a wider test with the percentage of manual tools being 50.00% and automatic hand sanitizers being 88.33%. Automatic hand sanitizer is expected to be able to maintain current health.